ANALISIS KUALITAS PELAYANAN PEMBAYARAN REKENING PDAM TIRTA BENING CABANG JUWANA KOTA KABUPATEN PATI - Orin Riana; Nina Widowati; Aloysius Rengga (Journal of Public Policy and Management Review, 2014)
PDAM is one company has duties and functions in organizing drinking water supply to all the society. Thus people use services PDAM, so the public has a duty routine a month in payment account. Service quality payment account PDAM Tirta Bening Juwana Pati district virtually less properly, resulting in a insatiability society to a performance given by the contamination. In this research was compiled to analyze a given quality of service offices in Juwana including dimensions that lead to less than optimal service. This research is descriptive research using this type of qualitative data collection techniques through observation, interviews, and in-depth study of the document. the informant was taken public as users of services and some of the officers PDAM.  In the research, the use writers five dimensions service quality namely dimensions tangible still signifying quality of being less well especially on providing facilities in support of service performance, dimensions reliability still signifying quality of being less well because human resource has not been done optimum dimensions responsiveness not signify good qualities because the officers in responding to customer problems still has sluggish yet responsive, dimensions assurance already signifying good qualities because pdam already guarantee cost according to the degree skill and the division of a group of customers. While dimensions empathy already signifying good qualities for concern officers on the good. Based on the research can be concluded that service quality payment account PDAM district starch virtually service quality less well or optimal for there is a mismatch between what people want with the quality imparted pdam in payment account so customer satisfaction has not come true. Therefore expected to done an improvement in some aspect dimensions not optimal especially in payment account with the online system the counter, the addition resources development of and availability of facilities sufficient; and others.